Indonesia’s Negotiation Strategy in Establishing Extradition Treaty with Singapore in 2022 - Amanda, Vania Tita; Hidayatullah, Nur Luthfi (The Sunan Ampel Review of Political and Social Sciences, 2023)
This study discusses the negotiation strategy used by the Government of Indonesia towards the Government of Singapore in establishing an extradition treaty. An extradition treaty is crucial for Indonesia to be able to try wanted fugitives who escaped to Singapore due to corruption cases. After decades of discussion, Indonesia and Singapore’s extradition treaty has finally reached an agreement in 2022 during Joko Widodo and Lee Hsien Loong’s leadership, due to preconditions given by both parties. This descriptive qualitative study uses the concept of collaborative negotiation strategy (win-win) developed by Lewicki, Barry & Saunders. The results of this research show that Indonesia’s negotiation strategy used during the leadership of President Joko Widodo used a collaborative (win-win) negotiation strategy, indicated by the fact that both parties could achieve the desired national interests. On one hand, Indonesia has established an extradition agreement, in addition to the Flight Information Region. On the other hand, Singapore has also established a Defense Cooperation Agreement as a precondition to the extradition agreement, in order to carry out military exercises in Indonesia’s territory. In conclusion, the negotiation strategy was successfully carried out by Indonesia, proven by the signing of the extradition treaty, which was further ratified by the People's Representative Council of the Republic of Indonesia.